Some Aspects of Modern Distance Learning Technologies in the Field of Fire Safety - V. V. Volodchenkova; N. V. Peregudova; D. N. Kurkin; O. V. Chirko (Открытое образование (Москва), 2022)
The article is devoted to the issues of distance learning of the basics of fire safety of the able-bodied population (employees of organizations). Traditional forms of education do not fully meet modern demands for knowledge in this area. The use of distance learning makes it possible to realize the needs for acquiring and updating the necessary competencies in the field of fire safety with the indirect interaction of a training specialist and a lecturer. The demand for this form of education, the effectiveness of learning the educational material largely depends on the ratio of digital technologies used in the educational process.The purpose of the study is to analyze modern technologies for organizing the educational process of distance learning in the basics of fire safety to improve the quality of educational services and motivate employees of organizations to study in a distance format. The constant development of computer technologies leads to the improvement of the distance learning format, the search for new methodological solutions.Materials and methods. The results of the study were obtained as a result of the analysis of existing developments and approaches to distance learning. The work on the organization of distance learning in general and teaching the basics of fire safety in this format to Russian and English-speaking researchers is considered. The analysis of best practices and technological innovations in the field of distance learning is carried out. The legal basis of the study is the normative legal acts of the Russian Federation. The methodological basis of the research includes methods of theoretical research (analysis, synthesis, generalization, modeling), graphic and comparative method.Results. The authors conducted a comparison of full-time and distance learning. The general characteristic factors, as well as the features of the distance-learning format are considered.Modern distance education technologies use software, hardware and educational theories to facilitate the learning process and increase the assimilation of knowledge. Thus, the virtual learning environment is a complex of computer technologies and pedagogical design, which allows having a qualitative impact on the formation and actualization of competencies in the field of fire safety. The organization of training in this format is an effective solution not only for the employee of the organization (the listener) but also for the lecturer. Distance learn- ing in the field of fire safety, organized based on a virtual learning environment, can provide pre-certification training for employees of organizations, and the lecturer can use modern training tools for the educational interaction.The authors propose a scheme of the educational environment for the listener, as well as the algorithm of the lecturer’s work in the format of distance learning in the basics of fire safety. Recommendations are given on the organization and presentation of educational material, taking into account the psychological characteristics of the perception of information, as well as the professional specifics of the listeners.Conclusion. The development of modern digital technologies has influenced the organization of training at all levels of education, including the professional training of employees of organizations. In order to achieve high educational results and acquire the necessary competencies in the field of fire safety, it is necessary to improve the system of digitalization of the educational environment, transformation of forms of material presentation and the introduction of innovative technological learning tools. High-quality training of specialists of organizations will have an impact on the formation of fire-safe behavior, reduce the risk of fire on the territory of the organization.